Factors associated with depression in patients with breast cancer - Arbulú-La Torre, Ximena Vanessa (2019)
Objective:Systematize the findings of studies on the factors associated with depression in patients with breast cancer.Methods:A systematic review of the medical literature was carried out in Medline, SciELO and Google Scholar with the descriptive terms of the Medical Subject Headings: depression, breast cancer. Six articles were selected with the exclusion criteria of articles with a publication period between 2013-2018, written in Spanish or English, which analyzed patients with depression associated with cancer breast and studies with a minimum sample of 80 participants.Results:In this review 6 have been includedstudies. The factors associated with depression in breast cancer patients we have is the age whereit is seen that the population between 40 and 60 years of age, being divorced or single, educational level up to primary school, being unemployed, belonging to a low social class, clinical stage 4 and chemotherapy treatment increases the risk of having depression in patients with breast cancerConclusion:It is concluded in the present review that more studies on a larger scale are needed regarding the factors associated with depression in patients with breast cancer, especially in Peru, since only one article related to the topic of interest was found. On the other hand, it is necessary to systematize the associated factors well since there are several factors related to depression and with different results depending on the type of hospital and country, to be able to propose a good program of psychological support and education about the disease.     DOI:  10.25176/RFMH.v19.n1.1795